IMPACT OF RECESSION ON RETAIL INDUSTRY IN INDIA - BAGWE, POOJA (2009)
Purpose- The intent of this study is to present a general overview about the current economic situation and various marketing activities undertaken by the retail industry during recessionary phase in India. Marketing plays a significant role in the retail sector and contributes a lot to the country. Thus, the aim of the study is to analyze the various marketing strategies employed by retail professionals during recession. The research presented here aims to find out the impact of Recession on the Indian retail sector and how this industry is dealing in such state of affairs.